Population estimates and spatial ecology of brown hyaenas in Kwandwe private game reserve - Welch, Rebecca Jane (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
During the last 25 years, the Eastern Cape Province of South Africa has seen the establishment of many small to medium sized (â‰¤ 440km2) game reserves. These reserves have reintroduced many of the larger indigenous wildlife that had been extirpated by the early 20th century. As such, these reserves and wildlife introductions have created many research opportunities, including investigations on the ecology of reintroduced carnivores in the Thicket biome. Brown hyaenas (Hyaena brunnea) are one of the large carnivore species that have been reintroduced into the area. As these animals have predominantly been studied in more open, arid systems, their reintroduction has provided an excellent opportunity to study the species in an alternate natural habitat. Information gathered from such investigations adds to our knowledge of the species and also provides information for the management of brown hyaenas within small, enclosed reserves. Data were collected over the period of one calendaryear, from February 2013 to February 2014 at Kwandwe Private Game Reserve in the Eastern Cape, South Africa. Brown hyaena population estimates were calculated using capture-recapture methods from individually identifiable images captured during a three month camera trapping survey. Images of brown hyaenas were separated into left- and right-side profiles. Twenty-eight individuals were positively identified from left-side images and 27 from right-side images. Non-spatial and spatially explicit capture-recapture analyses were both run in the program DENSITY 5.0. Density estimates ranged from 14 to 20 individuals/100km2 (equivalent to a total abundance of 26-37 individuals) depending on the method used. Despite the range of estimates, all are considerably higher than in other areaswhere densities have been calculated. Satellite/GPS collars were fitted to three individual brown hyaenas (two males and one female) to measure their home range size and use of space. Home range size was calculated using two different methods, Kernel utilisation distributions and Brownian bridges. Home range estimates were similar using both methods; however Brownian bridge methods appeared to exaggerate the use of space by individuals. Kernel home range sizes for the three individuals ranged between 42.62km2 and 79.88km2. These estimates are considerably smaller than previous findings from other parts of Africa and suggest that sufficient resources may be available within this enclosed system. The results from this study suggest that brown hyaenas are successful generalists in this enclosed system and are able to persist at high densities and occupy relatively small home ranges. This information is important for the managers of small reserves who wish to reintroduce brown hyaenas. Should brown hyaenas be introduced into reserves in the Thicket biome with sufficient resources, the numbers are likely to increase rapidly. If high numbers are not desired then preventative measures (e.g. contraception) should be investigated before release.
Keywords: Brown hyaena -- Reintroduction -- South Africa; Kwandwe Private Game Reserve